Metadata for Integrated Catalogue: Presidential Library experience - Zhlobinskaya, Olga N.; Selivanova, Yulia G. (Access: An International Journal of Nepal Library Association, 2024)
Integrated catalogue of the Presidential library is described, including heterogeneous resources (library, archival, museum) and collection-level descriptions for digital collections. Basic principles of the integrated catalogue are given such as: common metadata standard for various types of resources and their aggregations; consistent methodology for describing and indexing, taking into account the characteristics of each type and type of resources; use of common authority files to ensure the control of access points for names and subjects; and common search interface that provides access and viewing of diverse resources, digital collection being considered as one of types of resources. Main focus is using national metadata format RUSMARC as common metadata structure standard for various types of resources as well as for collection-level descriptions. It is shown that RUSMARC not only provides precise description and differentiation of various types of resources and their aggregations but also ensures structural compatibility of the descriptions and enhanced functionality of user search interface. RUSMARC metadata provides implementing single search box for all types of resources in the catalogue, using specific characteristics of each type of resource to further refine the search results.